EVALUATION OF TEACHER WELFARE IMPROVEMENT PROGRAM THROUGH PESANTREN HEALTH INSURANCE CIPP MODEL - Rohmah, Fitri Nur; Sayuti , Akhamad Fauzi (Jurnal Kajian Pendidikan dan Psikologi, 2024)
The low welfare of teachers is a big task for Islamic Education Institutions, especially Islamic boarding schools, to find solutions to improve their welfare. This research aims to measure the effectiveness of the health insurance and social security programs at the Mambaul Ulum Bata-Bata Pamekasan Islamic boarding school. The program's effectiveness is seen using program evaluation carried out using the CIPP (context, input, process, and product) model developed by Staflebeam.  The sources of research data are the person in charge of the program (Madamrosiyah Board of the Mambaul Ulum Bata-Bata Islamic boarding school), school principals, and teachers. The total population is 536 teachers. The sample was taken as 20% of the population, namely 107 people. Primary data was taken using questionnaires and interviews. The questionnaire instrument was tested with construct validity using correlation and Alpha Cronbach. Interviews were conducted with 3 school principals and 6 teachers divided into 3 male and 3 female teachers. Secondary data is obtained by documentation. The research results show that the program has been running effectively and on target. The aside (teachers) have felt the benefits of the program and are satisfied with the existence of this health insurance program because indirectly they worry that if they get sick and have to pay a lot of money can be covered by Islamic boarding school health insurance. The settlement amount is up to 70%. Therefore, this program is recommended for Islamic educational institutions such as Islamic boarding schools to improve their welfare in terms of health insurance. Findings also show that teachers who have received assistance tend to respond positively to the program compared to teachers who have never received assistance.